DETERMINASI EKSPOR NON MIGAS INDONESIA KE JEPANG - soeharjoto soeharjoto (Media Ekonomi, 2017)
This study aims to determine the factors that affect Indonesia's non-oil exports to Japan. The variables used are imports, exchange rates, per capita income, inflation and non-oil exports of Indonesia to Japan. The analytical method used is regression analysis with data used for quarterly time series data from 2005-2016. The results are variable imports of raw and auxiliary materials, cycles, inflation, real Japanese GDP, and the population is able to explain Indonesia's non-oil exports to Japan by 31.3 percent. Imports, exchange rates, per capita income and inflation have a positive and significant effect on non-oil and gas exports to Japan.